Labor of love : gestational surrogacy and the work of making babies - Jacobson, Heather (Families in focus., 2016)
Drawn from extensive interviews with paid gestational surrogates, women employed to carry children who are not genetically their own, Labor of Love reveals the challenges they face as they deal with complicated medical procedures, delicate work-family balances, and tricky social dynamics. The book demonstrates the extent to which advances in reproductive technology are affecting all Americans, changing how we think about maternity, family, and the labor involved in giving birth.